(untitled) (Avocetta, 2025)
Review of Van Nieuwehuyse D., van Harxen R. and Johnson D.H., 2023. The Little Owl. Population Dynamics, Behavior and Management of Athene noctua. 2nd Ed. Cambridge University Press 616 pp.